Dynamic response of beam-like composite sandwich plates with transversely flexible cores. (1st November 2015) - Mu, Lin; He, Bailing; Xiao, Dengbao; Zhao, Guiping; Cho, Chongdu
Abstract: This study is interested in adopting a simple way to analyze a dynamic response of beam-like composite sandwich plates with transversely compressible core under time-dependent impulse pressure. A two dimension (2-D) advanced model was proposed for the beam-like composite sandwich plate consisting of anisotropic skins and transversely compressible isotropic core. For validating the structural model developed in the present paper, the frequencies of sandwich panel predicted by the proposed models are compared with the results calculated from the finite element analysis by ABAQUS and the solution by some papers. Finally, the dynamic responses of the sandwich plate in terms of transverse displacements, deformation and stress of the sandwich plate under three kinds of time-dependent pressures (rectangular, delta and steady-state incentive) are discussed. Highlights: A two dimensional advanced model is proposed for beam-like sandwich panels. A simplified method is adopted to analyze the dynamic response of sandwich panels. The transversely flexible core shows a good ability to absorb energy.